(untitled) (Revista Española de Fisiología, 1967)
Kö 592 stops the action of the beta receptors, by acting on the same sites as propranolol. There exists a strong relationship between the dose of Kö 592 administered and the reduction in cardiac frequency obtained. The effective dose of Kö 592 required to decrease cardiac frequency by 50 % is 0.0788 mg/kg.